Analysis of the influence of GLONASS signals in the processing of one regional geodestic Network - Paniagua Jimenez, Diana (2018)
In recent years, there has been an increase in the number of satellites available for positioning using space techniques, highlighting the GPS and GLONASS systems. The comparative analysis of the results obtained from the calculation of a network of GNSS stations in Europe, from data processing using the Bernese 5.2 software, which, among other things, stand out for presenting an improvement in the joint treatment of GPS and GLONASS data with respect to the previous version of the program. The primary purpose that motivated the research is the need to determine whether or not the results of the combination of data from both systems are better than those obtained with version 5.0, since research has shown that the GNSS processing result in the Bernese 5.0 program tends to be less accurate than the result of processing with only GPS data. Consequently, it was found that the inclusion of GLONASS observables in the processing does not impact significantly on the results.